Comparative efficacy of tulathromycin and tildipirosin for the treatment of experimental Mycoplasma bovis infection in calves. Issue 3 (14th May 2016) - Bartram, David J.; Moyaert, Hilde; Vanimisetti, Bindu H.; Ramage, Clifford P.; Reddick, David; Stegemann, Michael R.
Abstract: The objective of this negative controlled, blinded, randomised, parallel group study was to compare the efficacy of two injectable macrolide antimicrobials, tulathromycin and tildipirosin, administered by single subcutaneous injection at dose rates of 2.5 and 4.0 mg kg −1 bodyweight, respectively, in the treatment of an experimentally induced Mycoplasma bovis infection in calves. A total of 238 M. bovis‐ negative calves were challenged on three consecutive days with M. bovis by endobronchial deposition. Post‐challenge, a total of 126 animals fulfilled the inclusion criteria and were randomly allocated to three treatment groups: tulathromycin, tildipirosin and saline. Clinical observations for signs of respiratory disease and injection site assessments were conducted daily for 14 days post‐treatment. The animals were then killed, the lungs were examined for evidence of lesions, and samples collected for bacterial isolation. Calves treated with tulathromycin had a lower percentage of lung with lesions ( P  =   0.0079), lower mortality ( P  =   0.0477), fewer days with depressed demeanour ( P  =   0.0486) and higher body weight ( P  =   0.0112) than calves administered tildipirosin. Abstract : The objective of this negative controlled, blinded, randomised, parallel group study was to compare the efficacy of two injectable macrolide antibiotics, tulathromycin and tildipirosin, administered by single subcutaneous injection at dose rates of 2.5 and 4.0 mg kg −1 bodyweight, respectively, in the treatment of an experimentally induced Mycoplasma bovis infection in calves. Calves treated with tulathromycin had a lower percentage of lung with lesions, ( P  = 0.0079), lower mortality ( P  = 0.0477), fewer days with depressed demeanour ( P  = 0.0486) and higher body weight ( P  = 0.0112) than cattle administered tildipirosin.